Pengembangan E-Modul Berbasis STEM Dengan Media Canva Untuk Meningkatkan Literasi Sains dan Numerasi Siswa SMP - Yatin, Yatin; Abidin, Zaenal; Arip, Asep Ginanjar (Peneliti.net, 2023)
Abstract Received: Revised: Accepted: This research was conducted to improve scientific literacy skills and numeration junior high school students with use material teach Which interesting And maximizing utilization technology. Quality Study Which low can improved with model learning Which interesting with utilize electronic media as a tool to help and support Learning Activities. The purpose of this study is to examine 1) Feasibility of E - Module , 2) E - Module Implementation , 3) E - Module Learning Effectiveness , 4) Response student to use E-Module based STEM with media canvas . Study This held start month April until May 202 3 . The population in this study are students class VII SMP Negeri 1 Mandirancan. The sample consists of 3 0 Class VII E as the experimental class and 3 0 class VII A students as class control. Design study Which used in study is a research development approach ( Research and Development ) with techniques data collection using tests, observations and questionnaires. Data analyzed with using SPSS software 22.0. The research results show 1) E-Module STEM -based with Canva media it is very suitable to be used as teaching materials in learning with an average score of 98.91% from material experts, 96.99% from linguists, 95.65% of media experts; 2) Implementation of E - Module Learning with Canva media gets an average percentage score of 88.33 in the good category; 3) effectiveness E - Module based STEM with media Canva uses _ formula effects size For ability literacy science with mark Chen 's d as big 3.67 and 1.27 for literacy numeration . Effect Size category of ability literacy science and numeration belong big which means it is effectively used as a teaching material; 4) Response student to learning use E-Module with medi a Canva falls into the strong criteria. The conclusions of this study are: 1) Based on expert validation, the feasibility of the E-Module is declared to be very suitable for use teaching materials; 2) The implementation of learning using E - Module with media a Canva very Good in increase ability literacy science and numeration students ; 3) There is a difference in increasing the ability of scientific literacy and significant numeration between experiment and control; 4) Students give positive responses to learning E-Modules with media Canva on Environmental Pollution material . Keywords: E-module based STEM , Media canva, Ability Literacy Science, Ability Literacy numeration . (*) Corresponding Author: How to Cite: Xxxxxx. (2018). Xxxx. Jurnal Ilmiah Wahana Pendidikan, XX (x): x-xx.